2021
DOI: 10.3389/fpsyg.2020.558466
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Assisted Self-Regulated English Language Learning: Associations With English Language Self-Efficacy, English Enjoyment, and Learning Outcomes

Abstract: This study investigated Chinese university students’ technology-assisted self-regulated learning (SRL) strategies and whether the technology-based SRL strategies mediated the associations between English language self-efficacy, English enjoyment, and learning outcomes. Data were collected from 525 undergraduate students in mainland China through three self-report questionnaires and the performance on an English language proficiency test. While students reported an overall moderate level of SRL strategies, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 70 publications
5
19
0
Order By: Relevance
“…The first two studies mostly focus on classroom-based learning, while the last study and this study put more emphasis on the online learning context. The result also agrees with the findings of other studies [22], [23]. Similar to this study, the Pearson's correlation analysis in [22] showed a positive and strong relationship, while [23] described a positive direction with a medium strength correlation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The first two studies mostly focus on classroom-based learning, while the last study and this study put more emphasis on the online learning context. The result also agrees with the findings of other studies [22], [23]. Similar to this study, the Pearson's correlation analysis in [22] showed a positive and strong relationship, while [23] described a positive direction with a medium strength correlation.…”
Section: Resultssupporting
confidence: 93%
“…The result also agrees with the findings of other studies [22], [23]. Similar to this study, the Pearson's correlation analysis in [22] showed a positive and strong relationship, while [23] described a positive direction with a medium strength correlation.…”
Section: Resultssupporting
confidence: 93%
“…The “Integrated English” course is typically delivered and assessed in English. While traditional and transmission-style teaching generally prevails in English Studies courses, efforts have been made in recent years to make it more student-centered in line with the “Quality Education” movement initiated by the Ministry of Education (An et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In current studies on students' use of information and communication technologies, self-efficacy appears as students' confidence in their ability to choose appropriate technological solutions and use selected technologies effectively to meet their learning needs (An, Wang, Li, Gan, & Li, 2021;Lai & Gu, 2011). Because a person's self-efficacy is fundamental when a skill is first learned, the development of current and future computer selfefficacy beliefs will be shaped on this basis (Connoly et al, 2018;Woolfolk Hoy, 2004).…”
Section: Computer Self-efficacymentioning
confidence: 99%